Kewarganegaraan dan Identitas: Menghargai Keberagaman dalam Kesatuan - M Tio Riyando; Budi Ardianto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The Purpose of this recearch is examines the dynamics of citizenship and identity in the context of diversity and unity in Indonesia, focusing on how the concept of inclusive citizenship can be effectively applied. Using a qualitative approach with a case study method, this research combines insights from political science, sociology and anthropology. Data was collected through in-depth interviews, participatory observation and policy document analysis. The research findings reveal that while there is a strong commitment to diversity in national policy, its implementation still faces significant obstacles, including a lack of understanding and awareness, discrimination against minority groups, and weak coordination between central and local governments. To address the gap between the ideal (das sollen) and the reality (das sein), this study recommends increased public education and awareness, empowerment of local and community leaders, better coordination between institutions, and strengthening of affirmative policies. By implementing these recommendations, it is hoped that Indonesia can more effectively value diversity and strengthen national unity, in accordance with the spirit of “Unity in Diversity,” which will ultimately create a more inclusive, just and harmonious society.